2018
DOI: 10.1002/14651858.cd012080.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diagnostic tests forHelicobacter pyloriinfection

Abstract: In people without a history of gastrectomy and those who have not recently had antibiotics or proton ,pump inhibitors, urea breath tests had high diagnostic accuracy while serology and stool antigen tests were less accurate for diagnosis of Helicobacter pylori infection.This is based on an indirect test comparison (with potential for bias due to confounding), as evidence from direct comparisons was limited or unavailable. The thresholds used for these tests were highly variable and we were unable to identify s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
130
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 1,110 publications
1
130
0
20
Order By: Relevance
“…43 A preliminary study from Brazil demonstrated that a 13 C-urea substrate synthesized by a local company could achieve the same performance in the UBT for the diagnosis of H. pylori infection as the substrate produced by foreign biotechnology companies. 45 44 Finally, Best et al performed a diagnostic test accuracy review on non-invasive diagnostic tests (UBT, serology, and stool antigen tests, SAT) for H. pylori infection.…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
“…43 A preliminary study from Brazil demonstrated that a 13 C-urea substrate synthesized by a local company could achieve the same performance in the UBT for the diagnosis of H. pylori infection as the substrate produced by foreign biotechnology companies. 45 44 Finally, Best et al performed a diagnostic test accuracy review on non-invasive diagnostic tests (UBT, serology, and stool antigen tests, SAT) for H. pylori infection.…”
Section: Urea Breath Test (Ubt)mentioning
confidence: 99%
“…Polymerase chain reaction (PCR) methodology has not been adopted as a routine test because of its technical demands and price compared to conventional tests. The common objection is the risk of false‐negative results due to mutations and false positives when nonspecific primers are used . The source of this opinion is an article by Sugimoto et al, who examined the detection limits for 26 PCRs (with different primers) using biopsy and saliva DNA samples when compared to data obtained from culture and histology results.…”
Section: Introductionmentioning
confidence: 99%
“…The latest H. pylori prevalence study in Thailand was reported in March 2018, which varied from 21 to 54%, but this study was conducted using expert opinions. 3,6,8,9 Currently, there are many recommended regimens in the guidelines for treating H. pylori infection. 6 Although the study is a systematic review, the prevalence was assessed from only one study in Thailand, with only 179 participants, using stool antigen as the diagnostic method; hence, it is not an appropriate representation of Thai populations.…”
Section: Introductionmentioning
confidence: 99%